Pelvic Ultrasound Parameters of Long-Acting Depot Formulation of Leuprorelin in the Treatment of Idiopathic Central Precocious Puberty in Girls - Yang K; Qi RF; Li RM; Zhang Y; Liu JX (Dove Medical Press, 2021)
Kun Yang,1 Rui-Fang Qi,2 Rong-Min Li,2 Yu Zhang,3 Jing-Xia Liu1 1Child Health Care Department, Baoding Children’s Hospital, Baoding, 071000, Hebei Province, People’s Republic of China; 2Endocrinology Department, Baoding Children’s Hospital, Baoding, 071000, Hebei Province, People’s Republic of China; 3Department of Science and Education, Baoding Children’s Hospital, Baoding, 071000, Hebei Province, People’s Republic of ChinaCorrespondence: Rui-Fang QiEndocrinology Department, Baoding Children’s Hospital, 3399 North Hengxiang Street, Lianchi District, Baoding City, 071000, Hebei Province, People’s Republic of ChinaTel +86 312 3377 771Fax +86 312 3377 800Email qiruifang_dr@163.comObjective: The present study was designed to compare the changes in ovarian and uterine parameters in girls with idiopathic central precocious puberty (ICPP) before and after gonadotropin-releasing hormone analogues (GnRHa) treatment to determine which sensitive indexes effectively reflect the therapeutic effect.Methods: Sixty girls diagnosed with ICPP were enrolled in the present study. Relevant data were recorded before treatment. Leuprorelin acetate microspheres were injected at a dose of 30– 180 μg/(kg four weeks). Relevant parameters were measured and recorded every three months. Changes in each parameter were analyzed to evaluate the clinical effect of leuprorelin in the treatment of girls with ICPP.Results: 1) The height grew at a constant rate. 2) The breasts retracted. 3) Changes in pelvic parameters: the volume of the ovary and uterus and major axes of the ovary, uterus, and cervix were reduced; there were no significant changes in vaginal thickness or the uterine fundal–cervical ratio (FCR). 4) Body mass index (BMI) increased.Conclusion: Pelvic ultrasound is helpful in evaluating the efficacy of GnRHA treatment. The changes of ovarian volume and the major axes of the ovary, uterus, cervix can be used as sensitive observation indexes.Keywords: leuprorelin microspheres, idiopathic central precocious puberty in girls, pelvic ultrasound, sensitive indicators